2019
DOI: 10.2147/ahmt.s209922
|View full text |Cite
|
Sign up to set email alerts
|

<p>Translating knowledge into action to prevent pediatric and adolescent diabesity: a meeting report</p>

Abstract: BackgroundThe obesity and Type 2 Diabetes Mellitus (T2DM) rates are at an all-time high globally. This diabesity epidemic is increasingly impacting children and adolescents, and there is scarce evidence of interventions with favourable long-term outcomes.PurposeIn order to understand the determinants of diabesity and how to address them, multiple stakeholders were invited to a meeting to discuss current state of knowledge and to help design a program to prevent pediatric and adolescent diabesity.Participants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
(37 reference statements)
0
2
0
1
Order By: Relevance
“…Nutrition, along with other factors such as physical activity, sleep, and mental health, should be considered in diabesity prevention. [ 57 ] It has previously been shown that saturated fats cause weight gain, hyperlipidemia, and insulin resistance. However, a low carbohydrate-high fat diet is more effective in comparison to a low-fat diet in reducing central fat,[ 58 ] indicating that focusing on fat alone is not enough.…”
Section: Metabolomics In Diabetesmentioning
confidence: 99%
“…Nutrition, along with other factors such as physical activity, sleep, and mental health, should be considered in diabesity prevention. [ 57 ] It has previously been shown that saturated fats cause weight gain, hyperlipidemia, and insulin resistance. However, a low carbohydrate-high fat diet is more effective in comparison to a low-fat diet in reducing central fat,[ 58 ] indicating that focusing on fat alone is not enough.…”
Section: Metabolomics In Diabetesmentioning
confidence: 99%
“…31 En el 2019 se observó que la Diabesidad afecta a la población en general. 32 En el 2018 se reportó que el 80% de los pacientes con DT2 fueron diagnosticados previamente con Obesidad. 33…”
Section: Tabla 2 Identificación De Antecedentes Y Consecuenciasunclassified
“…Acanthosis nigricans, polycystic ovarian syndrome, nonalcoholic fatty liver disease, and gout are also common associations of metabolic syndrome. Type 2 diabetes and obesity are the most closely related, and a common condition of "diabesity" occurs in both adults and children [20]. Obesity is a common risk factor for hypertension, and concomitant sleep apnea can contribute to hypertension.…”
Section: General Principlesmentioning
confidence: 99%